Lawbreaker - Palmer, Diana (Palmer, Diana. Long, tall Texans series, 2024)
"Tony Garza has been Odalie Everett's nemesis since the day they met. Once a New Jersey crime boss, Tony now owns an art gallery in New York, where he spends most of his time delegating his shadier business to subordinates. Odalie is a professional singer whose lifelong dream is to perform at the Met. She never expected to run into the heartbreaker from her past when she rents a small house near Tony's Manhattan apartment while taking voice lessons. But when they reconnect, they can't help but give in to unforgettable passion. As their relationship blossoms, deadly figures from Tony's past come back to exact revenge, and he'll do anything to protect Odalie...even bring her back home to her family ranch in Texas. But as Odalie struggles with the idea of leaving behind her dreams in the city to have true love in Texas, she finds herself caught in the ultimate trap--and Tony's past won't let them go."--